Science du gouvernement et manière de punir dans l’espace germanique : la conception pénale de Joseph von Sonnenfels et son évolution (seconde moitié du XVIIIe siècle) - Olivier Coelho (Criminocorpus)
During the second half of the 18th century, the penal question is being debated throughout Europe, which resulted in several reforms. Previous scholarship has seen in Joseph von Sonnenfels one of the prominent figures of that movement in the German territories. Historians especially underlined his opposition to the death penalty and torture. Sonnenfels was also one of the foremost exponents of the cameral sciences, a discipline aimed at defining the principles of good government that was becoming increasingly important in German universities at the time. In this article, I intend to analyze Sonnenfels’s penal reflections and their place in his thought about good government. In so doing, I try to understand how the European debate on penalty pervaded the cameral sciences.